Konseling Teman Sebaya Dalam Meningkatkan Fungsi Layanan Bimbingan Konseling di SMK Unggulan - Sri Wiworo Retno Indah Handayani; Nurfa Anisa; Rachmawati Rachmawati; Adri Marzuki (Universitas Negeri Gorontalo, 2026)
Guidance and Counseling (GC) services at SMK Diponegoro Tumpang, Malang, have not been optimally implemented due to the limited number of counselors and the low level of effective communication between students and counselors. Students tend to feel more comfortable sharing their problems with peers rather than with adults. This community service activity aimed to provide peer counseling training, increase student participation in utilizing GC services, and expand the scope of school-based GC services. The implementation method involved 42 students selected through a structured process, consisting of 21 students as prospective peer counselors and 21 students as counselees in the practice stage. The program was conducted in one day through three stages: preparation and selection, implementation, and evaluation. The results revealed three main outcomes, namely increased student participation and enthusiasm toward GC services, the successful implementation of peer counseling in real practice, and a positive impact on the overall function of school GC services. In addition, peer counselors actively supported early identification of students’ problems and fostered an atmosphere of openness within the counseling environment. This peer counseling program received positive responses from the school and is recommended to be sustainably integrated as a complementary approach to GC services in supporting students’ psychosocial development.